The myth of choice : personal responsibility in a world of limits - Greenfield, Kent (Yale University Press, 2011)
Americans are fixated on the idea of choice. Our political theory is based on the consent of the governed. Our legal system is built upon the argument that people freely make choices and bear responsibility for them. And what slogan could better express the heart of our consumer culture than "Have it your way"? In this book, the author poses unsettling questions about the choices we make. What if they are more constrained and limited than we like to think? If we have less free will than we realize, what are the implications for us as individuals and for our society? To uncover the answers, he taps into scholarship on topics ranging from brain science to economics, political theory to sociology. His discoveries, told through an array of news events, personal anecdotes, crime stories, and legal decisions, confirm that many factors, conscious and unconscious, limit our free will. Worse, by failing to perceive them we leave ourselves open to manipulation. But he offers useful suggestions to help us become better decision makers as individuals, and to ensure that in our laws and public policy we acknowledge the complexity of choice.